Segmentation of heart sound signal into cycles based on time properties of the heart sound - Mohd Zubir, Suboh; Mohd Yusoff, Mashor, Prof. Dr.; H. M., Hadi; A. R., Mohd Saad; M. S., Mohamed; B. T., Khor (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.